A Hybrid CFHR3-1 Gene Causes Familial C3 Glomerulopathy - Malik, Talat H. (American Society of Nephrology, 2012)
Controlled activation of the complement system, a key component of innate immunity, enables destruction of pathogens with minimal damage to host tissue. Complement factor H (CFH), which inhibits complement activation, and five CFH-related proteins (CFHR1–5) compose a family of structurally related molecules. Combined deletion of CFHR3 and CFHR1 is common and confers a protective effect in IgA nephropathy. Here, we report an autosomal dominant complement-mediated GN associated with abnormal increases in copy number across the CFHR3 and CFHR1 loci. In addition to normal copies of these genes, affected individuals carry a unique hybrid CFHR3–1 gene. In addition to identifying an association between these genetic observations and complement-mediated kidney disease, these results provide insight into the protective role of the combined deletion of CFHR3 and CFHR1 in IgA nephropathy.